Analisis Penilaian Kinerja Keuangan Unit Simpan Pinjam Pada Koperasi Serba Usaha Lorosae Makassar - Mardiana Ibrahim; Andi Bintang Balele; Wa Angga I (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine how the financial performance of the Lorosae Makassar Business Cooperative in terms of ratio analysis. Data analysis method used ratio analysis. The data collection methods use are library research, observation, interview and documentation.. The results of this study indicate the analysis of the overall liquidity, solvency and profitability ratios based on processed data shows that the financial performance of the Multipurpose Business Cooperative Lorosae Makassar for the period 2016, 2017 and 2018 has not been optimal or is not well assessed yet based on regulatory standards. The State Minister for Cooperatives.